Analisa Sistem Informasi Absensi Siswa pada SMP Santo Leo Jakarta - Bintang Dwinanto Prakoso; Ahmad Taufik (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
This study aims to analyze the student attendance system at SMP Santo Leo Jakarta and identify information technology-based solutions to enhance efficiency and accuracy in attendance recording. The school currently relies on a manual attendance system prone to recording errors, delayed reporting, and data manipulation. The research employed the Waterfall method, involving observation, interviews, questionnaire data collection, and literature study. The findings reveal that the manual system received low ratings, with average scores ranging from 40% to 42% in terms of usability, effectiveness, and functionality. However, the proposed technology-based system achieved a future expectation score of 80.74%, indicating the school's willingness to adopt a more modern system. An integrated attendance information system is expected to improve productivity, provide real-time information, and facilitate parental involvement in monitoring student attendance.